2013
DOI: 10.1007/s00431-013-2058-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice: Chronic fatigue syndrome

Abstract: The diagnosis chronic fatigue syndrome (CFS) was conceptualized in the mid-1980s. It is a clinically defined condition characterized by severe and disabling new onset fatigue with at least four additional symptoms: impaired memory or concentration, sore throat, tender cervical or axillary lymph nodes, muscle pain, multi-joint pain, new headaches, unrefreshing sleep or post-exertion malaise. Chronic fatigue syndrome in adolescents is a rare condition compared to symptomatic fatigue. The estimated prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…The FAI is derived from responses to questions asked during pregnancy and when the child was 8 to 10 years old regarding the following 9 factors, comprising 14 items in total: (1) age of mother at first pregnancy; (2) housing, comprising adequacy, basic amenities, defects, damp, and infestation; (3) mother's and father's low educational attainment; (4) financial difficulties; (5) relationship with partner, comprising lack of affection, cruelty, and lack of support; (6) social network, comprising lack of emotional support and lack of practical support; (7) substance abuse; (8) being in trouble with the police; and (9) psychopathology of the mother (anxiety, depression, or suicide attempts). Each of the 14 items is assigned a value of 1 if an adversity is present and 0 if it is not present; hence, the FAI has a theoretical range of 0 to 14.…”
Section: Family Adversitymentioning
confidence: 99%
See 1 more Smart Citation
“…The FAI is derived from responses to questions asked during pregnancy and when the child was 8 to 10 years old regarding the following 9 factors, comprising 14 items in total: (1) age of mother at first pregnancy; (2) housing, comprising adequacy, basic amenities, defects, damp, and infestation; (3) mother's and father's low educational attainment; (4) financial difficulties; (5) relationship with partner, comprising lack of affection, cruelty, and lack of support; (6) social network, comprising lack of emotional support and lack of practical support; (7) substance abuse; (8) being in trouble with the police; and (9) psychopathology of the mother (anxiety, depression, or suicide attempts). Each of the 14 items is assigned a value of 1 if an adversity is present and 0 if it is not present; hence, the FAI has a theoretical range of 0 to 14.…”
Section: Family Adversitymentioning
confidence: 99%
“…[1][2][3] CFS, also known as myalgic encephalomyelitis (ME) or, more recently, systemic exertion intolerance disease, 4 has been defined by using various diagnostic criteria. 5 Guidelines from the UK National Institute for Health and Care Excellence state that the diagnosis of CFS should be made after 3 months of persistent or recurrent fatigue that is not the result of ongoing exertion, not substantially alleviated by rest, has resulted in a substantial reduction in activities, and has no other known cause.…”
mentioning
confidence: 99%
“…Paediatric chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) is a condition, characterised by profound, unexplained chronic fatigue together with a range of other sleep, pain, cognitive, autonomic, neuro‐endocrine and immune symptoms. It causes significant morbidity at a crucial time in a young person's development . In a paediatric setting, it typically occurs during mid to late adolescence, a time associated with significant changes in social, cognitive, physical and biological development .…”
Section: Commonly Used Case Definitions For the Diagnosis Of Cfs/me Imentioning
confidence: 99%
“…It causes significant morbidity at a crucial time in a young person's development. 1,2 In a paediatric setting, it typically occurs during mid to late adolescence, a time associated with significant changes in social, cognitive, physical and biological development. 3 Disruption during this crucial development phase can lead to school absence, as well as long-term social, health, emotional, academic and vocational implications.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…
Werker et al [7] claim that several randomised controlled trials have demonstrated that cognitive-behavioural therapy (CBT) resulted in improvement and 'recovery' in 60-70 % of adolescent patients with chronic fatigue syndrome when assessed at 6 months [3,4,6], with 'comparable results at 2-3-year follow-up' [2,5]. However, I believe further data from the cited research studies would have been helpful to put the results in their full context.

The open-label FITNET trial [4,5] did indeed report a 63 % 'recovery' rate at 6 months.

…”
mentioning
confidence: 99%